Education of Self-actualization in Persian mystical texts - Ramin Moharami, Jafar Eshqi, Shokrullah Pouralkhas, Bizhan Zahiri Nav (Opción, 2019)
The aim of the study is to show the nature of the station of belovedness and to reveal the foundations of this station in the mystical thoughts. This essay has been authored based on a descriptive-analytic method. As a result, some of these masters, including Aynalquḍathamadani and Rūzbihān Baqli Shirazi have referred to two stations of loverhood and belovedness. As a conclusion, after we assayed the theories of masters of Sufism from the beginning until the time of Sultan Walad, we found out that the belief in such a station is rooted in Quran and also a tradition of Prophet.